Information competence as a key factor in continuous education of a leader (Journal of Educational Sciences, 2023)
Modern challenges require a dynamic transformation of the education management system. Thepurpose of the article is to describe the main approaches in the analysis of information and managementcompetence of the heads of structural divisions of a modern university. The methodological basis ofthe study is the results-oriented management methodology, a process-oriented approach, a systematicapproach in management, as well as the provisions of synergetic, acmeological, moderative and levelapproaches.The article discusses the features of the theoretical aspects of the study of information managementcompetence of managers, general criteria and factors for the development of information managementcompetence. The result of the study is a theoretical substantiation and comparative analysis of theconcepts of information and management competence of the heads of structural divisions of theuniversity.The scientific novelty lies in the fact that the material of the article contributes to the developmentof management theory, educational management, the system of professional development for heads ofstructural divisions of universities. 43 heads of structural subdivisions of the Al-Farabi Kazakh NationalUniversity took part in the pilot study.The practical significance of the article is related to the possibility of using the collected data inimproving the training of a new generation of higher education leaders with a high level of professionalism,competence, information and management culture. Key words: information culture, information worldview, information competence, informationliteracy, information and management competence of the head of the structural unit of the university,manager of the educational institution.